International Student Policies in Japan and South Korea in the Aftermath of the COVID-19 Pandemic - Ishikura, Yukiko; Tak, Yon-Soo (International Higher Education, 2024)
Higher education institutions in Japan and South Korea have strived to attract target numbers of international students. While each country had (nearly) reached its goals, the COVID-19 pandemic affected student flows. Recently, three years after the pandemic, the governments of Japan and South Korea announced new policies to reattract international student populations. This study examines how Japan and South Korea are reinvigorating their efforts.